Intermittent supply of dense water to the deep South Adriatic Pit: an observational study - Le Meur, Julien; Wirth, Achim; Paladini de Mendoza, Francesco; Miserocchi, Stefano; Cardin, Vanessa (Frontiers in Marine Science, 2025)
The renewal of bottom water masses in the deep South Adriatic Pit (SAP) is mainly determined by the arrival of very dense water that forms in the North Adriatic in winter (NAdDW) and which is transported into the SAP by gravity currents. To investigate the occurrence of these currents, we analyze high-frequency time series of thermohaline and velocity data at three moorings of the EMSO South Adriatic Sea regional facility, which consists of two observation areas: the SAP observatory (E2M3A) and the shelf and slope observatory (BB in the Bari Canyon and FF on the furrow area on the open slope), from 2012 to 2022, as well as reanalysis data from Copernicus over the same period. This analysis shows that gravity currents in the deep SAP (dSAP) only occurred in 2012, 2017, 2018, and 2022 (bottom ventilation years). The water masses were mixed differently after gravity current events, as 2012 was mainly driven by temperature, 2017 and 2022 by salinity, and 2018 by both. It was also found that in 2012 and 2018 the gravity current mainly passed through FF, while in 2017 it passed through BB. An analysis of the time scale showed that the average duration of the bursts of fluctuation triggered by the arrival of the gravity current in the dSAP was a few months (3 months on average). It was also revealed that the travel time from the formation of the NAdDW to BB was around 2 months on average, and that the travel time from BB (FF) to E2M3A was around 2 weeks. A comparison between the Copernicus reanalysis and the E2M3A time series also showed consistent differences in density, both in value and variability, resulting in the detection of gravity current events being unclear for the former.